Dissemination of Halal Certification, BPOM and Tax Reporting to Malingping Fish Meatball UMKM: English - Wahyudi, Tri; Refi Pratiwi; Intan Puspanita; Asih Machfuzhoh; Muhamad Fakhrudin; Muhammad Abduh; Galih Ginanjar Saputra (Kreativasi : Journal of Community Empowerment, 2023)
The purpose of this community service activity is to provide understanding regarding halal certification, BPOM and tax reporting to fishball business actors in Malingping District. This understanding is specifically related to the benefits obtained when fishball business actors implement the use of halal certification, BPOM and tax reporting. The methods used in community service include 1.) Lectures 2.) Tutorials 3.) Discussions. After this training is completed, fishball business actors can independently take care of halal certification, BPOM and make financial reports for tax compensation needs. The positive and enthusiastic response from the perpetrators of the Malingping Meatball business is an indicator of the success of this activity, and the potential for the Malingping Meatballs business actors is able to support business activities and improve business performance. economic independence from processed foods.